SUSTAINABLE PREMIUM OF SUSTAINABLE BONDS: EMPIRICAL STUDY OF STATE OWNED ENTERPRISES IN INDONESIA - Dimu, Darmia; Kim, Sung Suk (Universitas Multimedia Nusantara, 2025)
Abstract— This study investigates the sustainable premium of bonds issued by State-Owned Enterprises (SOEs) in Indonesia and examines the determinants influencing the yields of these sustainable bonds. Sustainable premium is the price difference of sustainable bonds and conventional bonds that are proxied by yield to maturity (YTM). A sustainable premium benefits issuers by reducing funding costs and building social capital. This study uses data panel regression for data analysis that taken from bonds that are listed on IDX in 2020-2023. The data consist of 1.018 bonds then sorted based on the type of bond (sustainable bonds and non-sustainable bonds) and the issuing company. It is found that the yield to maturity of sustainable bonds tends to be higher than conventional bonds. This means that based on the data there was no sustainable premium on SOE’s sustainable bonds in Indonesia. Meanwhile, the ESG risk score, status of SOEs, Return on Assets and Debt to Asset Ratio do not have a significant effect on the yield to maturity of SOEs’ sustainable bonds. Rating, modified duration, GDP and inflation have significant effects to yield to maturity of SOEs’ sustainable bonds. Keywords: Sustainable Premium; Sustainable Bonds; State Owned Enterprises; Yield to Maturity; ESG